"A short trauma course for physicians in a resource-limited setting: Is low-cost simulation effective?". Issue 9 (September 2015) - Pringle, K.; Mackey, J.M.; Modi, P.; Janeway, H.; Romero, T.; Meynard, F.; Perez, H.; Herrera, R.; Bendana, M.; Labora, A.; Ruskis, J.; Foggle, J.; et al.
Abstract Introduction Morbidity and mortality from intentional and unintentional injury accounts for a high burden of disease in low- and middle-income countries. In addition to prevention measures, interventions that increase healthcare capacity to manage injuries may be an effective way to decrease morbidity and mortality. A trauma curriculum tailored to low-resource settings was implemented in Managua, Nicaragua utilising traditional didactic methods and novel low-cost simulation methods. Knowledge gain in attending and senior residents was subsequently assessed by using pre- and post-written tests, and by scoring pre- and post-simulation scenarios. Materials and methods A 5-day trauma course was designed for Nicaraguan attending and senior resident physicians who practice at six hospitals in Managua, Nicaragua. On days 1 and 5, participants underwent pre- and post-training evaluations consisting of a 26-question written exam and 2 simulation cases. The written exam questions and simulations were randomly assigned so that no questions or cases were repeated. The Wilcoxon signed-rank test was used to compare pre- and post-training differences in the written exam, and the percentage of critical actions completed in simulations. Time to critical actions was also analyzed using descriptive statistics. Results A total of 33 participants attended the course, including 18 (55%) attending and 15 (45%) resident physicians, with a 97% completion rate. After the course, overall written examination scores improved 26.3% with positive mean increase of 15.4% (p < 0.001). Overall, simulation scores based on the number of critical actions completed improved by 91.4% with a positive mean increase of 33.67 (p < 0.001). The time to critical action for completion of the primary survey and cervical spine immobilisation was reduced by 55.9% and 46.6% respectively. Conclusions A considerable improvement in participants' knowledge of trauma concepts was demonstrated by statistically significant differences in both pre- and post-course written assessments and simulation exercises. The participants showed greatest improvement in trauma simulation scenarios, in which they learned, and subsequently demonstrated, a standardised approach to assessing and managing trauma patients. Low-cost simulation can be a valuable and effective education tool in low- and middle-income countries.